Synergistic impact of co-substrate of biodiesel crude glycerol and durian peel hydrolysate for biohydrogen and 1,3-propanediol synthesis by Clostridium butyricum - Sim, Xue Yan; He, Ning; Abdul, Peer Mohamed; Yeap, Swee Keong; Hui, Yew Woh; Jamali, Nur Syakina; Mong, Guo Ren; Woon, Kok Sin; Tan, Peng Chee; Tan, Jian Ping (Elsevier, 2024)
Aligning with Sustainable Development Goals 7 and 12, this project explores the utilization of durian peel and waste glycerol as sustainable carbon sources to produce green biohydrogen and 1,3-propanediol. The study elucidates the synergistic impact of the glucose-glycerol co-substrate ratio for the co-production of 1,3-propanediol and biohydrogen. Then, the ratio is applied to durian peel hydrolysate and biodiesel glycerol. A glycerol-to-glucose ratio of 10:1 by mass produces a maximum hydrogen productivity and yield of 67.46 mL/L∙h and 0.11 mol H2/mol substrate consumed and a fairly high 1,3-propanediol titer, yield and productivity. Moreover, the application of waste-derived carbon sources, i.e., durian peel hydrolysate and treated glycerol, enhances H2 yield and productivity by 18.9% and 7.5%, respectively. These findings promote biofuel and bioplastic application, establishing a flagship circular bioeconomy technology in the ASEAN region to cater to regional polyester, resin and energy demand while promoting waste reduction and lower greenhouse gas emissions.